2019
DOI: 10.1186/s13287-019-1296-8
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of human mesenchymal stem cells with different classes of vital stains: robustness and toxicity

Abstract: Background Mesenchymal stem cell (MSC) transplantation has been explored as a new clinical approach to repair injured tissues. However, in order to evaluate the therapeutic activity of MSC, cell tracking techniques are required to determine the fate of transplanted cells in both preclinical and clinical studies. In these aspects, different vital stains offer the potential for labeling and monitoring of grafted cells in vivo . It is desirable to have tracking agents which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…infusion of a preparation of nonmanipulated human stem cells “Neuro‐Cells” obtained from bone marrow, which are a combination of both mesenchymal stem cells (MSCs) and hemopoietic stem cells (HSCs). As both MSCs and HSCs have been shown to have the ability to differentiate into a spectrum of adult cell populations, many studies have sought to examine either the combined or individual contributions to repair in vivo in models of injury and potentially capitalize on the relationship between the two cell populations that is known to exist . As for instance, MSCs were shown to act as a feeder layer maintaining HSCs in an undifferentiated state.…”
Section: Introductionmentioning
confidence: 99%
“…infusion of a preparation of nonmanipulated human stem cells “Neuro‐Cells” obtained from bone marrow, which are a combination of both mesenchymal stem cells (MSCs) and hemopoietic stem cells (HSCs). As both MSCs and HSCs have been shown to have the ability to differentiate into a spectrum of adult cell populations, many studies have sought to examine either the combined or individual contributions to repair in vivo in models of injury and potentially capitalize on the relationship between the two cell populations that is known to exist . As for instance, MSCs were shown to act as a feeder layer maintaining HSCs in an undifferentiated state.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have shown that magnetic labeling of MSCs does not affect EV production in terms of the number of EVs, their size, as well as the presence of tetraspanins on their surface, which is also very positive information for the potential of cellular labeling and therapeutic transplantation of transplanted cells. This is important, as we have previously demonstrated that SPION has negligible impact on the MSCs’ stemness characteristic and their other properties in vitro [ 14 ]. Therefore, it seems that direct labels are quite resistant to packaging them to the EVs, so there is minimal chance that cell labeling will diminish EV-mediated positive therapeutic consequences of MSC transplantations.…”
Section: Discussionmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles (SPIONs) are quite versatile and relatively frequently used cellular label. It has been shown that SPIONs are mostly neutral to MSCs in vitro [ 318 ] and in vivo. [ 319 ] A very high signal of SPIONs, which allows them to be detected within seconds, is a major advantage.…”
Section: In Vivo Msc Imagingmentioning
confidence: 99%